Design considerations for rectangular bolted full face flanged joints for surface condensers - Augusto Soave; Miguel Mattar Neto (Brazilian Journal of Radiation Sciences)
Rectangular bolted full face flanged joints are widely used in surface condensers within the power generation industry including the nuclear one. In order to design these components, it is necessary to analyze the flanged joint from the point of view of structural strength and tightness. This work presents an analytical procedure applied to a rectangular bolted flange to determine the thickness of the flange, the bolt stresses and tightness conditions. First, the proposed analytical procedure is validated by comparing results from finite element analysis (FEA) using non-linear approach considering the behavior of the gasket and contacts. In addition, the results of proposed procedure applied to the design of a rectangular flanged joint of a steam surface condenser were compared for two different gaskets: compressed non-asbestos fiber gasket and NBR elastomer gasket. The results show a better performance of the NBR elastomer gasket in comparison with compressed fiber gasket: better sealing conditions, reduction of thicknesses of flange and reduction of bolt stresses. It is important to highlight there are practically no references of procedures for design non-circular full face flanged joints.